2019
DOI: 10.1186/s13018-019-1139-4
|View full text |Cite
|
Sign up to set email alerts
|

Guided growth with tension band plate or definitive epiphysiodesis for treatment of limb length discrepancy?

Abstract: Background It is not exactly known whether guided growth or definitive epiphysiodesis techniques are superior in treating limb length discrepancy (LLD). The purpose of the present study was therefore to find out if definitive epiphysiodesis is associated with more powerful LLD correction than tension band plate epiphysiodesis. Methods Pediatric patients with LLD treated either with tension band plating as a guided growth technique (temporary epiphysiodesis) or a percuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 14 publications
2
29
0
2
Order By: Relevance
“…Previous studies showed that the rate of correction after temporary epiphysiodesis is slower than after surgical physeal ablation. 4 6 This is confirmed here, with a correction rate of 0.40 mm/month (4.8 mm/year) for proximal tibial and 0.68 mm/month (8.2 mm/year) for distal femoral temporary epiphysiodesis. This is slightly less than the average growth of 6 and 10 mm/year of the proximal tibia and distal femur, respectively, that could be expected without any intervention.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Previous studies showed that the rate of correction after temporary epiphysiodesis is slower than after surgical physeal ablation. 4 6 This is confirmed here, with a correction rate of 0.40 mm/month (4.8 mm/year) for proximal tibial and 0.68 mm/month (8.2 mm/year) for distal femoral temporary epiphysiodesis. This is slightly less than the average growth of 6 and 10 mm/year of the proximal tibia and distal femur, respectively, that could be expected without any intervention.…”
Section: Discussionsupporting
confidence: 80%
“…On the basis of this lower efficacy as compared to other methods, some authors have discarded the use of tension-band plates for length correction completely. 4 6 Nevertheless, the speed of inhibition of longitudinal growth by itself might not be the most important benefit with this technique; the timing of the procedure is considered too. As stated by Stevens, the goal is to produce growth deceleration and not growth arrest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…New implants for guided growth (i.e., tension band plating with the 8-plate) were initially intended for angular deformity correction; nevertheless attempts were made to correct LLD. Based on the current literature, the application of tension band plates for LLD reduction cannot be recommended due to the lower correction potential with higher complication and revision rates [44][45][46][47]. Other implants designed for temporary ED (i.e., RigidTack TM ) ( Fig.…”
Section: Evidence In Lldmentioning
confidence: 99%